The Subtlety of Peace: A New Testament Challenge to Modern State Violence - Givens, Tommy (Studies in Christian ethics, 2018)
In order to offer a substantive Christian challenge to modern state violence, the particular character of the modern state cannot be ignored. Nor can New Testament teaching on peace be reduced to flat and generalized ethical imperatives. The subtlety of peace is neglected if either of these two tendencies goes unchecked. After thus framing the question of a Christian response to modern state violence, itself the product of Christian agency among other factors, I offer a New Testament challenge to modern state violence along two lines: (1) refusing the sacrificial political economy characteristic of the modern state, laboring instead at a christological dynamic of gift that takes account of the relative position of agents in the inherited distribution of power and expects more from the strong; (2) observing the limits of state representation for addressing vulnerability to violence, indeed its complicity in that vulnerability, and investing in scales of community commensurate with the subtlety of peace.